VDRL, TPHA, immunoglobulin in aborted and multipart woman’s in Baghdad governorate - AL-Husseinei, Raad Khalil; Kadaem, Khamael Majeed; AL-Janabi, Lamya Auwad; Fathei, Mun’im Mustafa (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Syphilis disease remain as a problem especially in developing countries. it can be detected by serological tests and the infection may affected the immunoglobulins concentration and may cause spontaneous abortion.